International journals of Library and Information Science in Scopus with high Spanish participation - Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2021)
In order to correctly interpret any study on Spanish production that includes Library and Information Science journals in citation indexes, it is necessary to know in detail what type of publications are being taken as source data. With this objective in mind, 12 foreign publications of this thematic category are analyzed in Scopus that have a higher degree of participation from authors attached to Spanish institutions. Most are owned by multinational publishing companies and are published in English. The production is very interdisciplinary, with a predominance of Scientometrics. As institutions, the CSIC and the universities of Granada, Carlos III of Madrid and Polytechnic of Valencia stand out. Scientometrics journal is the one with the largest number of works, followed by IEEE transactions on information theory and Investigación bibliotecológica. This case is the only magazine in Spanish of the 12 publications analyzed and the only title in which Library Science studies predominate.